Spatial distribution of ticks in Thailand: A discussion basis for tick-borne virus EXTENT assessment - C. Jean-Paul (2018)
A wide variety of viral infectious diseases are transmitted to humans through the ticks. Ticks are one of the key vectors for viruses coming from reservoirs such as wild or domestic animals. In certain cases, diseases resulting from tick-borne viruses can be very acute like encephalitis or haemorrhagic fevers. Within the framework of a research programme on emerging viral diseases carried out by the Development Research French Institute (IRD) in partnership with several counterparts in South-East Asia and more particularly in Thailand (Centre for Vectors and Vector-borne Diseases - Mahidol University), a location-based inventory of ticks using Global Positioning System technology appeared indispensable to attempt a first assessment of tick-borne viruses spatial distribution. Concurrently a literature review of acarology studies conducted through out Thailand over the entire 20 th century was completed. Hence, an almost exhaustive spatial distribution of existing ticks in Thailand was mapped. This Geographical Information System-aided analysis undertaken using SavGIS ® afi eeware GIS developed by IRD, is underpinned by a thorough knowledge on tick-borne arboviruses in Asia. This research represents a starting point for assessing tick-borne virus spatial distribution in Thailand. © Geoinformatics International.